Features and Origin of the Kızıldağ-Elazığ Mineralizations - Sağıroğlu, Ahmet (TMMOB Jeoloji Mühendisleri Odası [EN], 1986)
The Kızıldağ mineralizations occur within the granite of the Yüksekova Complex and are related to the faultings what generally strike E-W and dip to north. The mineralizations are either disseminated or as fillings of the fault zones and the type of mineralizations are specularite, pyrite (± chalcopyrite), galena (± sphalerite) and Cu minerals. The most common mineralizations are speciülarite and pyrite mineralizations what grades into each other. In the localities where Eh was high (above underground water table)’mineralizations formed as specularite and where Eh was low (below UWT) mineralizations took place as pyrite. The faulting took place during end of Upper Cretaceous - Palaogene and probably in the same period when the Keban metamorphics thrusted over the Yüksekova Complex. Although the outcropping parts of the mineralizations have no economic value, the mineral contents of the zones are likely to grade into valuable mineral assemblages vertically.

Kızıldağ cevherleşmeleri Yüksekova Karmaşığı içerisinde yer alan granit içerisinde ve genel olarak D-B doğrultulu ve kuzeye eğimli faylanmalarla ilgili olarak gelişmiştir. Cevherleşmeler genel olarak saçınımlı veya fay zonu dolgusu şeklinde gelişmiş olup cevherleşme türleri spekülaritit, pirit (+ kalkopirit), galen (± sfalerit) ve Cu mineralleri şeklindedir. En yaygın olarak spekülarit ve pirit cevherleşmelerine rastlanmaktadır. Eh değerlerinin yüksek olduğu yerlerde (YASS üstünde) spekülarit ve Eh'un negatif değerlere sahip olduğu yerlerde (YASS altında) pirit cevherleşmesi gelişmiştir. Bu iki cevherleşme birbirine geçiş göstermektedir. Faylanmalar Üst Kretase sonu-Paleosen'de, olasılıkla Keban Metamorfiklerinin Yüksekova üzerine bindirmesi sırasında gelişmiştir. Cevherleşmenin yüzeylenen kısımları ekonomik olarak önemli görünmemekte isede, düşey yönde cevherli zonların mineral içeriklerinin değişmesi kuvvetle olasıdır ve bu da cevherleşmelerin ekonomik olabileceğini göstermektedir.
Kızıldağ-Elazığ Cevherleşmesinin Özellikleri ve Kökeni
Keywords: Geological Sciences and Engineering (Other); Yer Bilimleri ve Jeoloji Mühendisliği (Diğer)